A Critical Review of Lexicography: Theoretical and Practical Issues - Saghar Sharifi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Lexicography: Theoretical and Practical Issues contains articles on lexicography by a group of reputable lexicographers. Modern lexicography in Iran is a new science, and there are few published works in this field in Persian. This, as well as some shortcomings in the selection and translation of these articles, prompted the author to refer to a few points and draw the reader’s attention to some of these issues in order to assist him in choosing the right work for his needs. In this critique, the features of this book are examined in terms of both formal and content aspects. In this review, the drawbacks of the book are mainly attributed to the selection of the articles and their non-alignment, the incorrectness of some of the equivalents, and their lack of uniformity.